Analisis Keputusan Pembelian Online Pada E-Commerce Shopee Ditinjau Dari Privasi, Keamanan Dan Kepercayaan - Fitrianingsih, Fitrianingsih; Fitriani, Hilda (STIE Bina Karya, 2024)
The aim of this research is to determine the influence of privacy, security and trust on online purchasing decisions on Shopee E-Commerce among the people of Pematang Kuing Village, Sei Suka District, Batu Bara Regency. The population in this research is all Shopee consumers who live in Pematang Kuing Village, Sei Suka District, Batu Bara Regency with a sample of 43 respondents. Hypothesis testing uses multiple regression analysis on the SPSS version 25 application. The results of this research show that partially privacy does not have a significant effect on the purchasing decisions of the people of Pematang Kuing Village, Sei Suka District, Batu Bara Regency. Meanwhile, security and trust have a significant influence on the purchasing decisions of the people of Pematang Kuing Village, Sei Suka District, Batu Bara Regency. Based on a simultaneous test, privacy, security and trust together (simultaneously) have a significant effect on the people of Pematang Kuing Village, Sei Suka District, Batu Bara Regency.